2009
DOI: 10.1292/jvms.71.759
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the Thoracic Duct with Injections of Dyes or Contrast Media into the Testicular Parenchyma in the Rabbit

Abstract: ABSTRACT. The thoracic duct drains lymph from the caudal part of the body to the venous system. The visualization of the thoracic duct is important for diagnosis of chylothorax, which may be caused by the damage of the duct. However, it is not easy to visualize the thoracic duct by injecting dyes and/or contrast media into peripheral lymph nodes and mesenteric lymphatics. In the present study, we examined whether the thoracic duct can be visualized by injecting dyes and contrast media directly into the testicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…It is thought that high-viscosity products have difficulties flowing through narrow lymph vessels. Tsuruno et al (2009) concluded that iohexol-240 is an optimal agent for TD visualisation in rabbits after intratesticular injection. As iohexol-240 is unregistered in our country, we used iohexol-350 (diluted in saline) to obtain a 245 mg/ml solution.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It is thought that high-viscosity products have difficulties flowing through narrow lymph vessels. Tsuruno et al (2009) concluded that iohexol-240 is an optimal agent for TD visualisation in rabbits after intratesticular injection. As iohexol-240 is unregistered in our country, we used iohexol-350 (diluted in saline) to obtain a 245 mg/ml solution.…”
Section: Discussionmentioning
confidence: 98%
“…Ashitate et al (2011) observed that MB injection into an inguinal LN resulted in successful TD visualisation in all pigs (8/8). When India ink or MB was injected in the testicular parenchyma of rabbits, TD was visualised in 3/3 patients (Tsuruno et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that the courses of efferent lymphatics may have a unique pattern in this species. Thus, we examined the patterns of courses of efferent lymphatics originating from the rabbit testis, by injecting India ink directly into the testicular parenchyma [11].…”
mentioning
confidence: 99%